PDF The Effect of Reputation, Halal COVID-19 Protocols, and Emotional Value on the Decision to Visit Halal Floating Market Tourist Destinations After the COVID-19 Pandemic: Pengaruh Reputasi, Halal Protokol Covid-19 & Nilai Emosional terhadap keputusan Mengunjungi Destinasi Wisata Halal Floating Market Setelah Pandemi Covid-19 - Cupian; Noven, Sarah Annisa; Fathi, Auliya; Afifah, Najla (Program Studi Ekonomi Syariah & LP2M STAI Az-Zain Sampang, 2025)
The COVID-19 pandemic severely impacted the tourism sector, causing a drastic decline in visitors and significant economic losses. However, halal tourism in Indonesia showed signs of resilience and recovery. A research gap exists in understanding the specific factors that influence tourists' decisions to revisit halal destinations, especially after a global health crisis. This study addresses this gap by investigating the combined effects of halal reputation, adherence to COVID-19 protocols, and emotional value on tourist behavior. This study aimed to determine the influence of halal reputation, COVID-19 protocols, and emotional value on the decision to visit the Floating Market in Bandung. Data was collected from residents of West Java who had previously visited the destination. The research employed a sophisticated structural modeling approach for data analysis. The findings reveal that all three factors have a strong and positive influence on tourists' intention to visit. A solid halal reputation builds trust and confidence among Muslim tourists. Strict adherence to COVID-19 protocols provides a crucial sense of safety and security. Furthermore, positive emotional experiences and friendly service significantly encourage tourists to return. These results suggest that focusing on these key factors is essential for the sustainable development of halal tourism.